A Review of Obsidian Source Exploitation in pre-Columbian South America - Periferakis, Argyrios (Bulletin of the Geological Society of Greece, 2019)
The focus of this paper is the obsidian quarries of the Pacific coast of pre-Columbian South America, which were exploited by the indigenous populations since ca. 11000 BC. The importance of obsidian in geoarchaeology and palaeoanthropology has already been demonstrated in sites from all around the world. In this paper, the presence of obsidian in correlation to tectonic activity and volcanism of South America is presented, along with the main sources in their regional geological context. Obsidian artefacts were the mainstay of everyday life of indigenous populations and obsidian was also used in manufacturing weapons. Despite advances in metallurgy, which were comparable with those of contemporary European states, obsidian was never supplanted by metal implements and weapons, until the Spanish conquest. Obsidian is as useful today, as it was to these civilisations, albeit in the different role, of discerning interactions between local societies, elucidating aspects of everyday life, and tracing palaeomobility and trade networks.